Interspecific protoplast fusion and liposome-mediated transformation in Streptomyces - Somasundaram, P.; Hopwood, D.A. (Malaysian Journal of Science, 1994)
Genetic recombination through protoplast fusion induced by polyethylene glycol (PEG) 1000 was investigated between various species of Streptomyces. The common parent Streptomyces coelicolor A3(2) strain 2709 (proA1 hisA1 argA1 cysD18 uraAl strA1), was fused with various strains of S. lividans, S. parvulus, S. albus G, S. violaceolatus and S. violaceoruber which were prototrophic and streptomycin sensitive. The fusions between S. coelicolor and the following species: S. parvulus, S. violaceoruber (2915) and S. violaceolatus gave clear negative results, while the fusions between S. coelicolor and S. lividans 66 strains 1326 and 2896 gave apparent recombination frequencies which ranged from 2.5 x 10 -8 to 1.0 x 10-6 . The reversion frequencies of the auxofrophic markers in the 2709 parent was about 1.0 x 10 -7 . Chromosomal marker recombination frequencies in an intraspecific protoplast fusion between strains 2709 and M145 ( S. coelicolor), both being SCP 1 - SCP2-, was 4.4 x 10-2 to 9.3 x 10 -2 . The recombinants selected were all streptomycin resistant. Interspecific liposome-mediated transformations of S. coelicolor 2709 protoplasts by donor DNA from S. lividans 66 1326 and 2896 indicated a 10 to 100-fold increase in the recombinant frequencies over that ofbrdinary protoplast fusions. The frequencies obtained during transformation with S. lividans 1326 DNA for the recombinants pro* stH; his+ stH, arg+ strr, cys+ strr and ura+ strr were 1.0 x 10 -6 to 1.0 x 10 -5, while those obtained with S. lividans 2896 DNA were 1.2 x 10 -5 to 3.5 x 10 -5